Pemberdayaan masyarakat melalui budidaya ikan dengan menggunakan pakan yang mengandung kunyit di Kelurahan Umban Sari Kecamatan Rumbai Pekanbaru - Morina Riauwaty; Windarti Windarti; Henni Syawal; Isma Mulyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Umban sari Village is one of Village in the Rumbai Sub Regency, Pekanbaru. This Village has a potential of fish culture in pont and in fish cages. The aim of this socialization is to understand the community empowering through fish culture using turmeric enriched pellets in Umban Sari Village, Rumbai Sub-Regency. The metode used are the preparation of the program, the manufacturer of the product, proximate analyses, socialization, monitoring and evaluation. The result shown that the society's empowerment is fish farmer in Umban Sari Village has the potential ability to make the turmeric enriched pellets.The result of monitoring and evaluation shown that the fish farmer in Umban Sari Village is committed to develop the turmeric enriched fish fed pellet processing as the effort of program sustainability.